Prevalence of Periodontal Bone Loss in Brazilian Adolescents through Interproximal Radiography - Benedicto Egbert Corrêa de Toledo; Eliane Marçon Barroso; Alex Tadeu Martins; Elizangela Partata Zuza (International Journal of Dentistry)
Purpose. The aim of this study was to verify the prevalence of alveolar bone loss in Brazilian adolescents through the interproximal X-rays analysis. Methods. Bilateral and standardized interproximal (bitewing) X-rays were performed in 15-year-old adolescents (), and the processing of films and measurements of alveolar bone levels were accomplished by a single examiner. A distance between the cementoenamel junction (CEJ) and the alveolar bone crest more than 2 mm was considered as periodontal bone loss. Results. The results showed percentage of bone loss of 10.4% with predominance of horizontal defects (8.9%) over the vertical types (1.5%). It was verified higher individual distribution of one lesion (67.6%) than two (26.5%) or three lesions (5.6%), and higher occurrence was detected in men (14.95) than in women (8.21). Conclusion. It can be concluded that the interproximal radiography was an efficient method for the detection of alveolar bone loss, revealing low prevalence in adolescents and predominance of horizontal bone defects.